PTU-157 A prospective study of serum vitamin A and D levels in primary bile acid diarrhoea. (28th May 2012) - Johnston, I; Pattni, S S; Nolan, J D; Dew, T; Walters, J R
Abstract : Introduction: There is evidence that primary bile acid diarrhoea (BAD) is caused by disruption of the homeostatic mechanism controlling bile acid synthesis, with an overproduction of bile acids leading to chronic watery diarrhoea. Fibroblast Growth Factor 19 (FGF19) has been shown to be central to this homeostatic mechanism, providing negative feedback on CYP7A1, the rate limiting enzyme in bile acid synthesis. Median serum FGF19 levels have been shown to be lower in BAD patients than in diarrhoea controls. In mouse models, it has also been shown that expression of FGF15, the orthologue of FGF19, is induced by the active forms of vitamins A and D. The aim of this study was to investigate a possible causal relationship between low serum levels of vitamins A and D and BAD. Methods: Patients with chronic diarrhoea were recruited prospectively. All patients underwent routine testing to exclude other causes of diarrhoea and had SeHCAT tests. Patients were classified as having primary BAD, secondary BAD, or unexplained chronic diarrhoea (CD). Serum 25OH-vitamin D was measured by LC-MS using standard procedures. Serum Vitamin A was calculated by HPLC. Results are expressed as medians. Mann–Whitney and Spearman rank correlation tests were used in analyses. Results: Serum vitamin A levels were available in 145 subjects (primary BAD 46; secondary 29; CD 70). Serum vitamin D levels were available in 150 subjects (primary BAD 50; secondary 29; CD 71). There were no significant differences in the level of vitamin A between the groups with primary or secondary BAD or CD (2.10, 1.90 and 1.95 umol/l respectively, p>0.05). There was no significant correlation of vitamin A with FGF19 or SeHCAT retention as a whole or within the subgroups. There were no significant differences in serum 25OH-vitamin D between the groups (38, 47, 46 nmol/l, p>0.05) There was no correlation of 25OH-vitamin D with FGF19 or SeHCAT retention as a whole, or within the subgroups. Conclusion: As vitamins A and D are known to induce FGF15 expression in mice, it was important to establish whether these vitamins could be associated with the abnormal FGF19 levels seen in human BAD. These results do not provide support to the possibility that deficiency of these vitamins is directly involved in the pathogenesis of BAD. Competing interests: None declared.